BASIC “STROKE APPROACH” IN PRE WRITTEN PROFICIENCY AMONG AUTISM CHILDREN AT QURANIS LEARNING CENTER IN TAWAU SABAH. (Proceedings of International Conference on Special Education, 2017)
Pre-writing skills are skills that involve sensory motor skills in fine motor control in the early childhood education. It can help children at an early stage in the strengthening of language proficiency through the aspects of writing. However, for children with autism, it is indeed a challenge to teach them the basic in pre-writing skills. An approach in using the basic strokes to teach basic Pre-writing skills to 8 autistic children in the Quranis Tawau learning center was conducted to help children through the early stage learning intervention. Introduction of basic stroke like sticks, humps and doughnuts are used as the basis of pre-writing skills used in the childhood learning activities. It is hope that the activities introduced can help in the early intervention of autistic children in the development of writing skills. In addition it can assist teachers in special education and early children education improved their teaching techniques in pre-writing skills that could be applied on children with autism in the future.